Tuberculosis considered as the ideal of beauty disease in romantic literature - Ouro Agromartín, María Dolores (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Known as phthisis, some countries had records of deaths from tuberculosis, although after the industrial revolution of the eighteenth century, records became frequent due to high mortality from tuberculosis. The causes were several: poor working conditions, unsanitary and crowded houses of human beings, the little varied diet, among others. The idealized image of tuberculosis will be defined through the study of various poems by authors who reflected the general thought of that time; a sampling of a disease that it continues to manifest itself, but without the added concept of romantic beauty.